A quantitative investigation of the absorption of certain cations by whole plants and plant tissues - Cresswell, Christopher Frederick (Rhodes University, Faculty of Science, Botany Department, 1959)
Introduction: Part 1. Greenhouse studies were conducted to investigate the absorption of sodium, potassium, calcium and magnesium by lemon seedlings. The plants were grown in controlled nutrient solutions and analysis of the plant material was made to determine the relationship between the four cations in the different plant organs. Results of the experiment may be summarized as follows:- The occurrence of leaf burn appeared to be associated with a low calcium content, together with a high sodium, potassium or sodium + potassium content. The development of the seedlings was shown to be markedly influenced by the level of calcium supply and to a much lesser degree by the level of potassium supplied. The concentration of sodium, potassium, calcium and magnesium in the stem and leaf varied with position of the tissues on the main axis. The level of sodium was found to influence the distribution of sodium in the leaves, and the sodium content of the leaf, stem and root tissues gave a good reflection of the level of sodium supplied. The effect of the sodium treatment on the uptake of potassium appeared to be dependent on the calcium content of the tissues. Sodium treatment was found not to affect the leaf calcium content. In the stem and root tissues the calcium content was reduced when the calcium level in the nutrient medium was low, and increased the calcium content of these two tissues at the higher level of calcium supply. The sodium supply was shown to reduce the leaf magnesium only slightly, and its affect on the magnesium content of the stem and root tissues was shown to be dependent on the level of calcium supplied. The potassium content of the leaves, stems and roots increased when the supply of potassium was raised. Increasing the potassium level in the nutrient supply was found to cause a very slight reduction in the sodium content of the leaf, but did not affect the sodium content of the stem and root. Potassium did not affect the calcium content of the leaves and increased the stem calcium when sodium was not present in the nutrient media in high concentrations. In the roots potassium only increase the calcium content at the upper level of calcium supply. The magnesium content of the leaf and stem tissues was reduced as the potassium supply was increased. In the roots the general trend was for the magnesium content to increase when the level of potassium treatment was raised. The calcium content of all the plant parts increased with a rise in the calcium supply, the stem and root tissues having a greater percentage increase than the leaves. The sodium content of the plant tissue was reduced as the level of calcium supply was raised. The leaf potassium content decreased with a higher calcium level of supply. In the stem and roots the potassium content was increased by doubling the calcium supply. The calcium treatment had no influence on the magnesium content of the foliage, but in the stem and root tissues a decrease in magnesium content resulted from an increase in the calcium supply. Part II Potato tuber tissue and carrot root tissue were used as experimental material in the investigation of sodium9 potassium9 and calcium uptake by storage tissue. It was shown that when the tissue disks are transferred from distilled water to a solution of salts there is a rapid initial uptake of cation which is neither particularly selective, nor related to metabolism, but dependent on the external concentration. On the other hand, the prolonged active accumulation of cation exhibits selectivity. Potassium absorption by potato tuber tissue was shown to be stimulated by sodium9 whereas the potassium and calcium absorption by carrot root tissue was shown to be reduced by sodium. Similarly the sodium absorption by the carrot root tissue was reduced by potassium, thus suggesting that the cations compete with one another for the same absorption mechanism.
Keywords: Cations -- Absorption and adsorption; Plant tissues